1997
DOI: 10.1046/j.1472-765x.1997.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic separation and conventional culture procedure for detection of naturally occurring Salmonella in raw pork sausages and chicken meat

Abstract: The aim of the study was to compare immunomagnetic separation (IMS) and conventional selective enrichment procedures using selenite cystine broth (SC) and Rappaport–Vassiliadis broth (RV) in 137 naturally contaminated food samples (69 raw pork sausages and 68 chicken meat). The utilization of SC or IMS appeared to be the most appropriate enrichment procedure: 15 out of 18 Salmonella‐positive samples (83·3%) were detected by SC and 12 (66·7%) by IMS; RV yielded only seven positive isolations (38·9%). However, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Our attempt to substitute selective enrichment by using IMS directly in the non-selective enrichment broth (EP1) was not successful. Previous attempts of reducing analysis time of conventional Salmonella detection methodology by using IMS after the non-selective enrichment of several types of foods were also unsuccessful (10,14). These results point out the importance of the enrichment step in novel methodologies for detection of salmonellae in foods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our attempt to substitute selective enrichment by using IMS directly in the non-selective enrichment broth (EP1) was not successful. Previous attempts of reducing analysis time of conventional Salmonella detection methodology by using IMS after the non-selective enrichment of several types of foods were also unsuccessful (10,14). These results point out the importance of the enrichment step in novel methodologies for detection of salmonellae in foods.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other studies have reported a poor performance of the method that combines IMS with plating on selective agar for Salmonella detection in chicken samples (13,14). The use of different enrichment protocols before IMS can be the cause of such contrasting results, since it is well known that selective agents of enrichment broths and incubation time and temperature are factors that affect decisively the analysis outcome (6).…”
Section: Resultsmentioning
confidence: 99%
“…Mansfield and Forsythe (7) and Molla et al (8) (11), which reported a poor performance of the IMS method in detecting Salmonella from, respectively, naturally contaminated raw sausages and poultry samples. The use of highly selective plating media can be one of the causes (4), since the selection pressure can make the growth of bacteria linked to the beads more difficult (5).…”
Section: Resultsmentioning
confidence: 99%
“…These factors lead to the decrease in sensitivity for IMS method, used to detect Salmonella bacteria [4] . Some researchers conclude this failure as both immunomagnetic particles are lost in meat with high fat content and as not using a medium with better selectivity [12,16] . In a study published by Mercanoğlu et al [20] , it was determined that anti-Salmonella globules could capture Enterobacter aerogenes, Escherichia coli and Klebsiella pneumoniae bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Under aseptic conditions, 25 g samples were taken, homogenised in 225 mL of Buffered Peptone Water (HiMedia, India) in a Stomacher (IUL Instrument, Spain) for 1 min and incubated at 37°C for 24 h [16] for pre-enrichment. Each culture was used for further testing with the three methods.…”
Section: The Detection Of Salmonella Sppmentioning
confidence: 99%